Molecular Characterization of the α-Glucosidase Gene (malA) from the Hyperthermophilic Archaeon Sulfolobus solfataricus - Rolfsmeier, Michael (American Society for Microbiology, 1998)
Acidic hot springs are colonized by a diversity of hyperthermophilic organisms requiring extremes of temperature and pH for growth. To clarify how carbohydrates are consumed in such locations, the structural gene (malA) encoding the major soluble α-glucosidase (maltase) and flanking sequences from Sulfolobus solfataricus were cloned and characterized. This is the first report of an α-glucosidase gene from the archaeal domain. malA is 2,083 bp and encodes a protein of 693 amino acids with a calculated mass of 80.5 kDa. It is flanked on the 5′ side by an unusual 1-kb intergenic region. Northern blot analysis of the malA region identified transcripts for malA and an upstream open reading frame located 5′ to the 1-kb intergenic region. The malA transcription start site was located by primer extension analysis to a guanine residue 8 bp 5′ of the malA start codon. Gel mobility shift analysis of the malA promoter region suggests that sequences 3′ to position −33, including a consensus archaeal TATA box, play an essential role in malA expression. malA homologs were detected by Southern blot analysis in other S. solfataricus strains and in Sulfolobus shibatae, while no homologs were evident in Sulfolobus acidocaldarius, lending further support to the proposed revision of the genus Sulfolobus. Phylogenetic analyses indicate that the closest S. solfataricus α-glucosidase homologs are of mammalian origin. Characterization of the recombinant enzyme purified from Escherichia coli revealed differences from the natural enzyme in thermostability and electrophoretic behavior. Glycogen is a substrate for the recombinant enzyme. Unlike maltose hydrolysis, glycogen hydrolysis is optimal at the intracellular pH of the organism. These results indicate a unique role for the S. solfataricus α-glucosidase in carbohydrate metabolism.